2011
DOI: 10.1111/j.1365-2036.2011.04922.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of ambulatory pH monitoring do not reliably predict response to therapy in patients with eosinophilic oesophagitis

Abstract: SUMMARY BackgroundThe consensus statements for eosinophilic oesophagitis recommend that ambulatory pH monitoring is one means of determining if gastro-oesophageal reflux is the cause of oesophageal eosinophilia and should guide pharmacological therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 17 publications
2
65
1
1
Order By: Relevance
“…Efforts to further distinguish EoE from PPI-REE have proven difficult. Endoscopic and clinical characteristics appear to be similar [58]. Earlier studies by Francis et al have shown that even ambulatory pH monitoring is not reliable in predicting response to PPI [59].…”
Section: Proton Pump Inhibitor Responsive Esophageal Eosinophiliamentioning
confidence: 77%
“…Efforts to further distinguish EoE from PPI-REE have proven difficult. Endoscopic and clinical characteristics appear to be similar [58]. Earlier studies by Francis et al have shown that even ambulatory pH monitoring is not reliable in predicting response to PPI [59].…”
Section: Proton Pump Inhibitor Responsive Esophageal Eosinophiliamentioning
confidence: 77%
“…Second, a discrepancy exists between symptomatic and histologic remission. Some patients do not present symptom relief even after endoscopic and histological improvement has been achieved [59,110,111]. This discrepancy is likely attributed to the limited response of the sub-epithelial fibrosis and remodeling to the currently available medication.…”
Section: Treatmentmentioning
confidence: 85%
“…However, subepithelial fibrosis or muscle dysfunction is difficult to detect by a conventional endoscopic approach with a biopsy. This may partially explain the discrepancy between the degree of clinical symptoms and the severities of endoscopic abnormalities or histological eosinophilic inflammation in EoE [59][60][61][62]. Esophageal foreign body impaction is a major GI emergency in Western countries, where EoE with food impaction is more common.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Current thinking suggests that eosinophilic oesophagitis is an immune-mediated, antigen-driven disorder; 3 thus, diet elimination and/or corticosteroid therapy would seem the fitting therapeutic strategy. 4 There is now, however, confirmatory evidence available, including our study 2 and their data, 5,6 as well as other studies, [7][8][9][10][11][12][13][14][15] that symptomatic patients with oesophageal eosinophilic infiltration, which is phenotypically indistinguishable from eosinophilic oesophagitis, respond to PPI therapy. In further support of Drs.…”
mentioning
confidence: 85%